Clinical Significance of an HPV DNA Chip Test with Emphasis on HPV-16 and/or HPV-18 Detection in Korean Gynecological Patients - Min-Kyung Yeo; Ahwon Lee; Soo Young Hur; Jong Sup Park (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background: Human papillomavirus (HPV) is a major risk factor for cervical cancer. Methods: We evaluated the clinical significance of the HPV DNA chip genotyping assay (MyHPV chip, Mygene Co.) compared with the Hybrid Capture 2 (HC2) chemiluminescent nucleic acid hybridization kit (Digene Corp.) in 867 patients. Results: The concordance rate between the MyHPV chip and HC2 was 79.4% (kappa coefficient, κ = 0.55). The sensitivity and specificity of both HPV tests were very similar (approximately 85% and 50%, respectively). The addition of HPV result (either MyHPV chip or HC2) to cytology improved the sensitivity (95%, each) but reduced the specificity (approximately 30%, each) compared with the HPV test or cytology alone. Based on the MyHPV chip results, the odds ratio (OR) for ≥ high-grade squamous intraepithelial lesions (HSILs) was 9.9 in the HPV-16/18 (+) group and 3.7 in the non-16/18 high-risk (HR)-HPV (+) group. Based on the HC2 results, the OR for ≥ HSILs was 5.9 in the HR-HPV (+) group. When considering only patients with cytological diagnoses of "negative for intraepithelial lesion or malignancy" and "atypical squamous cell or atypical glandular cell," based on the MyHPV chip results, the ORs for ≥ HSILs were 6.8 and 11.7, respectively, in the HPV-16/18 (+) group. Conclusions: The sensitivity and specificity of the MyHPV chip test are similar to the HC2. Detecting HPV-16/18 with an HPV DNA chip test, which is commonly used in many Asian countries, is useful in assessing the risk of high-grade cervical lesions.